Bacteriological profile of surgical site infections in a tertiary care hospital of western Nepal - Dharm Raj Bhatta; Abhijit Adhikari; Jampa Lhamo Gurung; Niroj Man Amatya; Niranjan Nayak; Shishir Gokhale (Journal of Gandaki Medical College, 2021)
Introduction: Surgical site infections are one of the most commonly reported nosocomial infections resulting into significant morbidity and mortality. Hospital admission and surgical procedures increase the risk of infection with multidrug resistant pathogens. This study was aimed to determine the bacterial agents associated with surgical site infections and antibiotic resistance patterns of the isolates.